The effects of aquatic and land-based interventions on children with developmental coordination disorder - Ferreira, Lúcio Fernandes; Souza, Cleverton José Farias de; Oliveira, Jorge Alberto de; Freudenheim, Andrea Michele (Frontiers in Human Neuroscience, 2025)
BackgroundKnowledge about the effects of aquatic intervention on children with developmental coordination disorder (DCD), as well as the maintenance of these effects over time, is still scarce. We believe that there is a need to advance our knowledge of this subject, for which we have set ourselves the following objectives: (1) to test whether the effects of aquatic and land-based interventions influence the motor performance of children with DCD; (2) to check whether these effects persist over time; and (3) whether the effects of aquatic and land-based interventions bring motor performance values closer together between children with DCD and those with typical development.Methods76 children aged between 6 and 10 years old were divided into four groups, control developmental coordination disorder (C-DCD); control typical development (C-TD); experimental terrestrial developmental coordination disorder (T-DCD); and experimental aquatic developmental coordination disorder (A-DCD). Due to some dropouts, the final sample consisted of 66 children, 27 girls and 39 boys. The groups of children with DCD were randomized according to their initial total score on the Movement Assessment Battery for Children Test - second edition (MABC-2). The analysis of variance (one-way ANOVA) carried out in the pre-test showed similarity between the means of the DCD groups (C-DCD, T-DCD and A-DCD), which ensured that these groups started from the same performance level. The interventions lasted 4.5 months (18 weeks) with three sessions a week, totaling 54 sessions of 60 min each. The experimental groups took part in the same intervention protocol, with the only difference being the environment (A-DCD = aquatic environment; T-DCD = terrestrial environment).ResultsAnalysis of the results revealed no significant effect for the group and time point interaction, F(6, 133) = 1.36, p = 0.235. However, effects were detected for group, F(2, 54.7) = 3.78, p < 0.05, and for time point F(3, 131) = 22.91, p < 0.001. The Tukey-Kramer post-hoc test found a difference between the T-DCD and C-DCD groups (p < 0.05; independent-groups effect size (dig = 0.85; dig = 0.87; dig = 0.92). For time point, differences were found between the pre-test and the other time points [post-intervention (repeated measures effect size) (dR,M = 1.14), 3 months post-test (dR,M = 1.51) and 6 months post-test (dR,M = 2.2)] with a significance level of p < 0.001. For the A-DCD group there was no statistically significant difference in relation to either the C-DCD or T-DCD group, but we did observe large effect size values [pre-test and post-test (dR,M = 1.14), pre-test and 3 months-post-test (dR,M = 1.29) and pre-test and 6 months-post-test (dR,M = 1.61)]. Regarding the analysis of the Z score, the results indicated an interaction effect for the group and time point F(6, 132) = 2.30, p = 0.038. This difference was located by post hoc between the C-DCD group and the A-DCD (p < 0.05; independent groups pre-test - post-test effect size (digpp = 1.72) and dig = 0.79) and T-DCD (p < 0.05 ES digpp = 1.65 and dig = 0.79) groups at 6 months-post-test.ConclusionWe conclude that both aquatic and terrestrial interventions have positive effects on the motor performance of children with DCD, that these effects are maintained over time but also bring the motor performance of children with DCD closer to that of children with typical development.